Development and Validation of a Versatile UPLC-PDA Method for Simultaneous Determination of Paracetamol, Tizanidine, Aceclofenac, and Nimesulide in Their New Combinations - Sami Bawazeer; Khalid M. Badr El-Din; Ahmed M. Abdel-Megied (Journal of Analytical Methods in Chemistry)
A simple, rapid, and validated UPLC method was developed for the simultaneous quantitation of paracetamol (PAR), tizanidine (TIZ), aceclofenac (ACF), and nimesulide (NIM) either in pure forms or in their different tablet dosage forms. Chromatographic separation was attained on an ACQUITY UPLC™ BEH C18 column (100 mm × 2.1 mm, 1.7 μm) with a mobile phase consisting of 20 mM phosphate buffer (pH 7.0) : acetonitrile in the proportion (60 : 40 v/v) isocratically pumped at a flow rate of 1.25 mL·min−1, and detection was monitored at 305 nm. All analytes were separated simultaneously at a retention time (tr) of 1.42, 2.31, 3.63, and 5.62 min for PAR, TIZ, ACF, and NIM, respectively, with a total run time less than 6.0 min. The proposed method was validated according to ICH guidelines with respect to accuracy, precision, linearity, limit of detection, limit of quantitation, and robustness. Linearity was obtained over a concentration range of 81.25–487.5, 0.5–3.5, 25–150, and 25–150 µg·mL−1 for PAR, TIZ, ACF, and NIM, respectively. The development method can be successfully employed in QC laboratories for the routine analysis of the investigated drugs in their new combination.